2012
DOI: 10.1371/journal.pone.0030996
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide DNA Copy Number Analysis of Serous Type Ovarian Carcinomas Identifies Genetic Markers Predictive of Clinical Outcome

Abstract: Ovarian cancer is the fifth leading cause of cancer death in women. Ovarian cancers display a high degree of complex genetic alterations involving many oncogenes and tumor suppressor genes. Analysis of the association between genetic alterations and clinical endpoints such as survival will lead to improved patient management via genetic stratification of patients into clinically relevant subgroups. In this study, we aim to define subgroups of high-grade serous ovarian carcinomas that differ with respect to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 96 publications
3
33
0
Order By: Relevance
“…These investigators defined a subtype of high-grade ovarian cancer characterized by up-regulation of immune response genes, with worse survival (both overall survival (OS) and progression-free survival (PFS), P < 0.001) than endometrioid ovarian tumors or serous tumors of low grade, early stage and low malignant potential. Another previous study identified amplified regions mapping to 12p12.1, 19q12, 20q11.21 and 20q13.12 with significantly worse outcomes (OS, P = 0.0028; PFS, P < 0.001) [20]. For comparison to our data, the region of 12p12.1 amplified in both A-H- and S-H-specific gains overlapped with the regions of the previous study, indicating a worse outcome.…”
Section: Resultssupporting
confidence: 65%
“…These investigators defined a subtype of high-grade ovarian cancer characterized by up-regulation of immune response genes, with worse survival (both overall survival (OS) and progression-free survival (PFS), P < 0.001) than endometrioid ovarian tumors or serous tumors of low grade, early stage and low malignant potential. Another previous study identified amplified regions mapping to 12p12.1, 19q12, 20q11.21 and 20q13.12 with significantly worse outcomes (OS, P = 0.0028; PFS, P < 0.001) [20]. For comparison to our data, the region of 12p12.1 amplified in both A-H- and S-H-specific gains overlapped with the regions of the previous study, indicating a worse outcome.…”
Section: Resultssupporting
confidence: 65%
“…The 53 microdissected, high-grade advancedstage serous ovarian adenocarcinoma samples for the expression profiling have been described previously (5). The 25 high-grade, late-stage, serous ovarian tissue specimens used to investigate the potential correlation between FGF18 and microvessels or TAM infiltration were available FFPE samples from the CGH study (16). A validation tissue microarray was constructed with 263 FFPE samples obtained from patients with informed consent at the MGH between 1993 and 2009.…”
Section: Methodsmentioning
confidence: 99%
“…16 and Figure 1C and Supplemental Figure 2). Compared with the previ- ous study (4), a similar rate of 5q31.3-5q35.3 amplification was observed in approximately 25% of the patients and an average copy number of 4 was shown in both FGF18 and its potential receptor FGFR4 (located in chromosome 5q35.2, Figure 1C and Supplemental Figure 2).…”
Section: Fgf18 Predicts Survival In Patients With High-grade Advancementioning
confidence: 96%
“…Interestingly, CCNE1 amplifications are mutually exclusive with BRCA1 / BRCA2 mutations in HGSOC, suggesting that their respective impacts on genomic stability are either redundant or synthetically lethal (7). Unlike BRCA1/BRCA2 -mutant tumors, which initially respond to platinum-based chemotherapy, CCNE1 -amplified tumors are associated with primary platinum failure (1214). Given the lack of treatment options for these patients, it is important that we interrogate the mechanisms by which CCNE1 contributes to HGSOC initiation, progression, and drug resistance, in order to identify potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%